3-1.2k=-1.2k+3

Simple and best practice solution for 3-1.2k=-1.2k+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-1.2k=-1.2k+3 equation:



3-1.2k=-1.2k+3
We move all terms to the left:
3-1.2k-(-1.2k+3)=0
We get rid of parentheses
-1.2k+1.2k-3+3=0
We add all the numbers together, and all the variables
=0
k=0/1
k=0

See similar equations:

| -7x-29+21x=5-(12-2x) | | 16x*9x=100 | | 7r-4R=18 | | -5+4n-7=40+5n | | 33(11+x)=21(-1+x) | | 2.3+7.2x=3.2+3.7x | | y/8-3/4=1/2 | | 4x+(12-2x)=24 | | -6(2w-4)+3w=7(w+6) | | 2x-12=-4x+6 | | 63-2x=79-3x | | Z+8z=9 | | x-x(.10)=56772 | | -5+4n+n=-40+5n | | -4x+30=23(x+33) | | 4x-2+2(5x+3)=-4(x+1) | | 2/5(n)=12 | | -3=x-5/6 | | 4p+3=3(p-2) | | -3/4x+1/4=13/4 | | -7g-5=8+3g-2 | | 1/3.x=20 | | -4w-11=18 | | 3x+5x+4-x+8=88 | | 3(w-3)-4=-2(-8w+2)-7w | | x-8/11=-2 | | 2(6x-8)=40+4x | | -5+4n+n=2n+15 | | -9=3w+4(w+3) | | -5g(-1)(8-g)=12 | | 7q-9=40 | | 18=5u+2(u-5) |

Equations solver categories